Modeling the Transmission Dynamics of HIV/AIDS epidemics: an introduction and a review. - Onoja Matthew Akpa; Benjamin Agboola Oyejola (Journal of Infection in Developing Countries)
Introduction: One of the greatest causes of morbidity and mortality in the Sub-Saharan Africa, particularly among young adults, is HIV/AIDS. Many mathematical models have been suggested for describing the epidemiology as well as the epidemiological consequences of the epidemic. A review of some these models would aid researchers in applying them to better understand and control the incidence and distribution of the disease in their countries.